State regulation of modernization of higher education and science in the conditions of European integration (Economics and region, 2024)
The article, based on the analysis of legal acts, analytical materials and published scientific works of scientists of Bulgaria, Poland and Ukraine, and the study of the practice of educational reforms, examines the problems of state regulation of the modernization of higher education and science in the conditions of European integration in post-communist countries. the task of the research is to identify effective methods and directions of state regulation of the modernization of the higher education system in the conditions of European integration with the aim of proposing them for use in Ukraine. The relevance of this problem is confirmed by reference to the experience of foreign countries. The importance of reforms is determined by the need to maintain and develop a high level of education of the population, as it contributes to achievements in all spheres of life. At the same time, it is necessary to take into account the coherence of different educational levels both among themselves and from the point of view of the development of science. A review of sources and literature was carried out. A significant number of publications were noted and previously undisclosed aspects of the topic were identified. Challenges in the field of science and higher education are highlighted in the comparative table. The similarity of many problems related to the socialist past and the need to carry out a complex of reforms was noted. The specifics depend primarily on the economic development of the country and the level of its integration into the European Union. As a common feature of the modernization of higher education and science, internationalization as a result of the influence of globalization, digitalization, and Europeanization is highlighted. Changes related to student-oriented education, marketing, massification, and management are characterized. The need to increase the autonomy of higher educational institutions and increase attention to taking into account the needs of teachers aimed at the modernization of education and science was noted. Key problems for teachers are named: low level of remuneration, busyness with current duties; high norms of educational, scientific, educational and organizational workload do not allow to realize their potential of mobility and creativity. It was emphasized that the state should create conditions for the modernization of higher education and science. The author also notes the connection between the level of education and the democratic processes taking place in the country and the level of its economy.
Keywords: public administration; higher education; modernization; state regulation; European integration